Importance of cassava processing for production in subSaharan Africa - Nweke, F.I.; Bokanga, M. (International Society for Horticultural Science, 1994)
This paper is based on information collected from about 600 villages in the ten largest cassava-producing countries within the framework of the Collaborative Study of Cassava in Africa (COSCA). The objective of the paper is to show that growth in cassava production in the region will depend more on improvement in processing technology than on breeding for low cyanogenic potential. The paper shows that in the region, cassava is produced for sale. Most of the cassava produced is processed to improve quality and reduce marketing costs and hence make cassava competitive with food grains in the market. Farmers therefore select cassava genotypes for postharvest attributes. Whether the cassava variety has high or low cyanogenic potential is not important to such farmers so long as the variety has other derived attributes. There are, however, certain population groups which need varieties with low cyanogenic potential for specific reasons.